Legal Safeguards for Owners of Untapped Foreign Brands Under Indonesia's First-to-File Principle: Perlindungan Hukum bagi Pemilik Merek Asing yang Belum Dimanfaatkan Berdasarkan Prinsip First-to-File Indonesia - Artija, Arfiansyah Dewa; Purwaningsih, Sri Budi (Indonesian Journal of Law and Economics Review, 2024)
This study examines the risks associated with unregistered trademarks, particularly in the context of Indonesia's adherence to the First To File principle. Employing normative methods with a statistical and statutory approach, data was gathered from Supreme Court Decision and DGIP Brand websites to identify potentially problematic and non-problematic brands. Results reveal three layers of legal protection for foreign brand holders outlined in TRIPS regulations, the Paris Convention, and Law no. 20 of 2016, each with its own limitations. Moreover, the study delineates two forms of legal safeguarding for brands: preventive measures through regulatory frameworks and repressive actions via sanctions for infringements. These findings underscore the importance of registering trademarks for robust protection, emphasizing the need for comprehensive legal strategies to mitigate risks for brand owners in the global marketplace. highlights : The study elucidates the vulnerabilities associated with unregistered trademarks within the framework of Indonesia's First To File principle. It identifies and examines the legal safeguards available to foreign brand holders under TRIPS regulations, the Paris Convention, and Indonesian Law no. 20 of 2016. The research underscores the significance of comprehensive legal strategies, including preventive measures and repressive actions, to protect brand owners in the global marketplace. Keywords: Unregistered trademarks, Legal protection, Brand ownership, Intellectual property rights, First To File principle.